Roles of Community-Based Fisheries Management and Marine Reserves in Coastal Fisheries - Alcala, Angel C. (Silliman Journal, 2023)
This paper discusses the roles of organized and empowered communities and marine reserves in the management of coastal fisheries, with special reference to the Philippines. It will attempt to show the advantages of the community approach and the need for the establishment of marine reserves in the management of coastal fisheries